A3_2 Locking Aircraft engine fans - Karazhov, Dennis; Ryan, Liam; Booth, Tim (Physics Special Topics, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> In this paper we investigate the behaviour of a typical passenger commercial aircraft when its control has been lost by the pilot due to failure of electronic systems. We also introduce the possibility of manually locking the engine fans, such that additional air resistant area is introduced, and also look at how this method changes the trajectory and velocity.